Application of the environmental impact assessment provisions under the BBNJ Agreement in high seas marine protected area: challenges and suggestion - Wang, Yong; Pan, Xin (Frontiers in Marine Science, 2025)
Once the BBNJ Agreement enters into force, its environmental impact assessment (EIA) provisions will apply to high seas marine protected areas (MPAs). This paper examines current treaties and practices within four high seas MPAs and finds that the EIA provisions established by United Nations Convention on the Law of the Sea (UNCLOS) are ambiguous. The BBNJ Agreement, however, reflects a strong commitment to improving EIA laws and practices in Areas Beyond National Jurisdiction (ABNJ). Despite this progress, several challenges may arise in implementing the BBNJ Agreement’s EIA provisions in high seas MPAs. These include potential fragmentation when members of the international frameworks or bodies (IFBs) of high seas MPAs do not ratify the agreement, uncertainties surrounding the “not undermine” proviso, and ambiguities in the “due regard” principle. Additionally, the Clearing-House Mechanism (Cl-HM) under the BBNJ Agreement requires further development to cooperate with the institutions of high seas MPAs, and the fragmented EIA standards, subjects and procedures for high seas MPAs complicate the determination of equivalency with those under the BBNJ Agreement. Moreover, the EIA provisions for existing high seas MPAs appear limited. It is worth mentioning that the practices of the EIA in high seas MPAs may not be sufficient. This paper offers several recommendations for the above challenges: encouraging non-Parties to apply the EIA provisions under the BBNJ Agreement, putting forward a possible interpretation or understanding for the “not undermine” proviso and “due regard”, developing the CL-HM through the BBNJ Secretariat, and developing EIA guidelines for high seas MPAs, supported by the Scientific and Technical Body set by the BBNJ Agreement. Furthermore, members of the IFBs of high seas MPAs should enhance their EIA practices to ensure effective application of the BBNJ Agreement’s provisions in the future.